Dystonia, Chorea, and Ataxia: Three Challenging Cases - Pedroso, José Luiz; Vale, Thiago Cardoso; Meira, Alex Tiburtino; Braga-Neto, Pedro; Barsottini, Orlando G. P.; Espay, Alberto J. (Seminars in Neurology, 2022)
Movement disorders comprise a heterogeneous and complex group of neurological disorders that increase (hyperkinetic) or decrease (hypokinetic) the speed or amplitude of movements, or disrupt their coordinated sequencing. In this article, we describe three instructive cases, exemplifying classic movement disorders, namely dystonia, chorea, and ataxia. We highlight the diagnostic approach based on clinical clues, syndromic reasoning, evaluation, and management recommendations. Each case ends with key messages for the clinicians.
Keywords: movement disorders; diagnostic reasoning; dystonia; chorea; ataxia